2000
DOI: 10.1175/1520-0469(2000)057<2542:cstc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Composite Ship Track Characteristics

Abstract: The physical and radiative properties of a composite ship track are described from the analysis of 131 shipship track correlation pairs collected during the Monterey Area Ship Track experiment. The significant variability of ship tracks around their average characteristics is also described. The nominal environmental conditions for the ship track set are also described. The composite ship track is 296 Ϯ 233 km long, 7.3 Ϯ 6 h old, and averages 9 Ϯ 5 km wide. The ship is, on the average, 16 Ϯ 8 km from of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 14 publications
9
76
0
Order By: Relevance
“…For a pixel to be classified as low cloud, a temperature threshold was used. Durkee et al (2000b) present measurements of the height of low stratiform clouds which are modified by ship emissions. The cloud top height never exceeded 1500 m in these measurements.…”
Section: Ship Track Mask Algorithmmentioning
confidence: 99%
“…For a pixel to be classified as low cloud, a temperature threshold was used. Durkee et al (2000b) present measurements of the height of low stratiform clouds which are modified by ship emissions. The cloud top height never exceeded 1500 m in these measurements.…”
Section: Ship Track Mask Algorithmmentioning
confidence: 99%
“…See the footnotes for details on the single cases. Durkee et al (2000a) discuss a case of vertical plume dilution where first bright clouds (indicative of the ship pollution reaching the top of the MBL) appear about 1400 s after plume release in a 400 m deep MBL. Based on this, our "best guess" for β is 0.6.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This leads to a chemical lifetime of about 2 days. Note that the mean lifetime of 7.3 h that was derived during the MAST campaign (Durkee et al, 2000a) is based on a different definition, namely on cloud albedo effects as measured from satellites. The most dramatic reductions in pollutant concentrations of course occur during the first hour after plume release.…”
Section: Effects Of Emissions Of a Single Shipmentioning
confidence: 99%
“…The MAST experiment studied ship tracks for one month off the coast of California. The results gained from the analysis of 131 ship tracks produced by known ships showed that the average ship track had length 296±233 km and width 9±5 km (Durkee et al, 2000a). Ship tracks are rarely found in cloud at an altitude above 1 km (Coakley et al, 2000).…”
Section: E Campmany Et Al: Detection Of Ship Tracks In Atsr-2 Satelmentioning
confidence: 99%
“…These conditions include a small boundary layer depth, pre-existing cloud formation mechanisms, and CCN concentrations below a threshold value. The MAST study returned average values of wind speed of 7.8 ms −1 , surface pressure of 1018.3 mb and surface temperature of 287.8 K (Durkee et al, 2000a). Albrecht (1989) proposed one further effect ship tracks could have on cloud cover, and hence the climate: a reduction in drizzle.…”
Section: E Campmany Et Al: Detection Of Ship Tracks In Atsr-2 Satelmentioning
confidence: 99%